The response of the azimuthal component of the ionospheric electric field to auroral arc brightening - Safargaleev, V.; Lyatsky, W.; Gazey, N. G.; Smith, P. N.; Kriviliov, V. (CCSD, 2000)
International audience We have analyzed the response of azimuthal component of the ionospheric electric field to auroral arc activity. We have chosen for analysis three intervals of coordinated EISCAT and TV observations on 18 February, 1993. These intervals include three kinds of arc activity: the appearance of a new auroral arc, the gradual brightening of the existing arc and variations of the arc luminosity. The arcs were mostly east-west aligned. In all cases, the enhancement of arc luminosity is accompanied by a decrease in the westward component of the ionospheric electric field. In contrast, an increase of that component seems to be connected with arc fading. The observed response is assumed to have the same nature as the "short circuit" of an external electric field by the conductor. The possible consequence of this phenomenon is discussed. Keywords. Ionosphere (electric fields and currents; ionospheric irregularities) · Magnetospheric physics (auroral phenomena)